Sajak-sajak Realisme Sosialis Lekra: Kajian Tematik - Suyono Suyatno (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2011)
Lekra poems basically reflects the aesthetics of socialist realism which is adoped by the Lekra in the art and literature, including also in poetry. The aesthetic of socialist realism seems to be built from the oppositions between capitalist/imperialist–socialist, bourgeois–the proletariat with the partisanship on the part of the latter. To realize the partisanship that belong to the ideology of Marxism and socialism, Lekra also utilizing statements which are hyperbolic. Thus, the actual poems of Lekra identical with the mouthpiece of the communist party who spread propaganda.